Open Heart Surgery in Haseki Training and Research Hospital: Evaluation of the First 500 Cases - Mazlum Şahin; Cihan Yücel; Fatma Tuğba İlal Mert; Semi Öztürk (Haseki Tıp Bülteni, 2018)
Aim: The purpose of this study was to evaluate outcomes of the first 500 open heart surgeries performed in the Department of Cardiovascular Surgery at Haseki Training and Research Hospital, which was founded in 2014. Methods: Records of 500 open heart surgeries performed between December 2014 and February 2017 were evaluated retrospectively. A total of 374 patients underwent coronary artery bypass grafting, 11 Bentall operation, 41 aortic valve replacement, and thirty eight patients underwent mitral valve replacement (MVR). Tricuspid ring annuloplasty was performed in four patients who had previously undergone MVR and atrial septal defect closure in 12 patients, while five patients were operated due to cardiac myxoma and 20 patients due to type 1 aortic dissection. Results: The mean age of the patients was 57.6±13.1 years (17-84 years). Hypertension (54.4%) was the most common comorbidity, followed by hyperlipidemia (43.1%), diabetes mellitus (34.36%), Chronic Obstructive Pulmonary disease (21.5%), and peripheral arterial disease (9.3%), respectively. In-hospital death occurred in 22 of 480 (4.58%) patients and 10 of 20 patients (50%) who were operated due to type 1 aortic dissection. The overall hospital mortality rate was 6.4% (26 of 500 patients). Conclusion: Our experience showed that world class cardiac care is provided in our center.